SELECTION AND EVALUATION OF A STABILIZER COMPOSED OF RUBBERS ON QUALITY PROPERTIES IN MIXTURES FOR HARD ICE CREAM - POSADA DAVID M.Sc., Liliana Rigey; SEPÚLVEDA VALENCIA M.Sc., José Uriel; RESTREPO MOLINA M.Sc., Diego Alonso (Vitae, 2012)
Background: Today’s market demands ice cream with excellent texture and body properties, which together with the taste, determine to a large extent the acceptability of these. In this industry there is a marked tendency towards the use of integrated stabilizers that will enhance synergism between components, obtaining better quality end products. Objetives: The present work aims at evaluating the effect of a carob, karaya and guar gum mixture, as thickening agent, on some quality characteristics (bromatological, sensory and stability) of hard ice creams. Methods: The research was conducted in two stages; in the first one is evaluated the effect of individually gums (100%), binary mixture (50:50 %) and ternary mixtures (33.3: 33.3: 33.3 %), applied at a level of 0.3% (w/w) in the hard ice-cream mix system. In the second stage, it is evaluated the effect of level of application in hard ice-cream mix, at testing levels of 0.3, 0.35 and 0.4% (w/w) of the mixture 50% carob gum and 50% guar gum, compared against a witness who had a commercial stabilizer applied in 0.3% (w/w), which resulted in four treatments. Results: With the results of the first stage it is performed the determination of thixotropy, which allowed us to establish as best mixtures the one corresponding to the proportion 50% carob and 50% guar gum and the 100% guar gum mixture, according to the response surface methodology. The final ratio of prices allowed choosing guar: carob gum for application, along with the fact that such combination made possible evaluating behaviors and interactions as a mixture. In the second stage, the results show that the ice cream formulated by mixing 50% carob gum and 50% guar gum, shows a lower percentage of melting and less time in the fall of the first drop compared to the control. The treatment 0.4% presents grater gumminess, while the control a higher roughness. The flavor quality is significantly diminished over time, in all treatments. Conclusion: The selected mixture of carob and guar gum, has positive influence on the evaluated characteristics against the commercial stabilizer of ice cream.